Switching to the Mac : the missing manual - Pogue, David, 1963- (Missing manual., 2005)
Demonstrates how to become adjusted to the Macintosh operating system and how to transfer data from a Windows system to a Macintosh, discussing topics such as moving files and Macintosh equivalents to Windows-only programs.